(untitled) (Annals of Bangladesh Agriculture, 2024)
Bangladesh has embraced digitalization to the point where social media has become an essential tool for communication among all sectors of people, including agriculture. The current study was, therefore, attempted to ascertain the extent of use of various social media platforms by the farmers. The study was conducted in two Upazilas viz. Sreepur and Gazipur Sadar Upazila of Gazipur district. A total of 100 farmers were selected as a sample of the study following a proportionate random sampling technique. Four-fifths (80.0%) of them had poor to moderate knowledge of social media use. Among the digital social media, Knowledge on smartphones ranked first. The use of different social media by the majority (84.0%) of respondents was impressive, where 33.0 percent had low use and 51.0 percent moderate. Watching the Hridoye Mati O Manshu program on Facebook / YouTube ranked 1st position for using agricultural purposes. In the case of non-agricultural purposes, the use of Messenger / Imo / WhatsApp to communicate with relatives/friends ranked in 1st position. Moreover, around half of the respondents (51.0%) preferred Facebook among other social media due to its multidimensional usage. The majority of the respondents showed as moderate users (4-9 years) of different social media using experiences. The vital preference of using social media is to communicate with others, followed by ’entertainment’ and ’ease of handling’. Level of education, farm size, and annual income showed a positive significant relationship with the extent of use of different social media by the farmers, while age and farming experience indicated a negative significant relationship. ’Network problems’, ’load shedding’, ’high cost’, ’poor Wi- Fi’ service, and ’addiction to overuse of social media’ were some of the major problems identified by the respondents in using social media. Ann. Bangladesh Agric. (2023) 27 (1): 105-120